A boy called Slow : the true story of Sitting Bull - Bruchac, Joseph, 1942-; Baviera, Rocco (New York : Putnam & Grosset Group, 1998)
The true story of the childhood of the Lakota hero, Sitting Bull, and how he received his name.
"PaperStar.".
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
Wilson's Children.
Book Links (A.L.A.), December 2002.
Booklist, March 1995.
Keywords: Sitting Bull, -- 1834-1890 -- Juvenile literature; Sitting Bull, -- 1834-1890.; Sitting Bull, -- 1834-1890.; Dakota Indians -- Biography -- Juvenile literature; Dakota Indians -- Biography; Indians of North America -- Biography; Dakota Indians -- Biography; Native Americans -- United States -- Biography